HRV IN EVALUATION OF PROCESSES OF ADAPTATION IN NEWBORNS - Tsoy, Ye.G.; Igisheva, L.N.; Galeev, A.R. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The aim of this study was to clear up the peculiarities of adaptation in early neonatal period. Comparative analysis of clinical and rythmographic data was made in 122 full-term newborns at the age of 1-6 days. Undulating course of adaptation process characterized by increasing of life activity in the first two days and on the 6-th day and relative of functional activity on 3-5-th days was estimated. Dimension of measurement of heart rate variability (HRV) allows us to characterize course of adaptation in early neonatal period.